Prevalence of human papillomavirus and Helicobacter pylori in esophageal and gastroesophageal junction cancer biopsies from a case–control study in Ethiopia - Maria E. Leon; Endale Kassa; Abate Bane; Tufa Gemechu; Yared Tilahun; Nigatu Endalafer; Sandrine McKay-Chopin; Rosario N. Brancaccio; Gilles Ferro; Mathewos Assefa; Elizabeth Ward; Massimo Tommasino; et al. (Infectious Agents and Cancer, 2019)
Abstract Background Ethiopia lies in the high-risk corridor of esophageal squamous cell carcinoma in East Africa, where individuals with this malignancy often do not report established risk factors, suggesting unidentified etiologies. Here, we report the prevalence of mucosal human papillomavirus (HPV) and of Helicobacter pylori (H. pylori) detection in endoscopy-obtained esophageal and gastroesophageal junction biopsies and in oral cell specimens taken at the time of esophageal cancer diagnosis in a case–control study in Addis Ababa, Ethiopia. Methods DNA extraction was performed from fresh frozen tissue and oral cell pellets obtained with saline solution gargling subsequently fixed with ethanol. Mucosal HPV and H. pylori DNA was detected using highly sensitive assays that combine multiplex polymerase chain reaction and bead-based Luminex technology. The proportions of specimens testing positive were expressed as percentages, with binomial 95% confidence intervals. Agreement of results between tissue biopsy and oral cell specimens was estimated using the kappa statistic. Comparison of study participants’ characteristics by test results was done using the Pearson chi-square test. Results HPV DNA was detected in 1 of 62 tumor specimens (2, 95% confidence interval (CI): 0–9%), corresponding to HPV16 type. HPV DNA was detected in the oral cavity of 7 cases (11, 95% CI: 5–22%) and 4 of 56 matched healthy controls (7, 95% CI: 2–17%), with multiple HPV types detected. Detection of H. pylori DNA was 55% (95% CI: 42–68%), and 20 of 34 H. pylori-positive specimens (59, 95% CI: 41–75%) were positive for the cagA gene. Agreement of detection rates between tissue and oral cells in cases was poor for HPV and for H. pylori. Conclusions The prevalence of mucosal-type HPV was very low, whereas H. pylori was more commonly detected, with a high proportion testing positive for the pro-inflammatory gene cagA. These novel findings remain to be replicated in larger studies and with the addition of serological determinations to better understand their biological significance in the context of esophageal and gastroesophageal junction cancers.